2020
DOI: 10.1038/s41598-020-68726-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure and distribution of chalky deposits in the Pacific oyster using x-ray computed tomography (CT)

Abstract: Oysters are unusual among bivalves in that they possess chambers, often filled with soft, chalky calcite, that are irregularly scattered throughout the shell. Because the function of these so-called chalky deposits is still unclear, evaluating the growth and distribution of chalk is important for elucidating the ecological function of this unique shell trait. Specimens of the Pacific oyster Magallana gigas, an oyster well known for chalk expression, were grown in Bodega Harbor, Bodega Bay, CA. At the end of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Cross section of the juvenile shell shows two prominent micro-structures—the prismatic layer just below the periostracum, and folia layer which forms the major fraction of the juvenile shell (figure 2 f ). The chalky layer could not be observed in these early juvenile shells [51].…”
Section: Resultsmentioning
confidence: 99%
“…Cross section of the juvenile shell shows two prominent micro-structures—the prismatic layer just below the periostracum, and folia layer which forms the major fraction of the juvenile shell (figure 2 f ). The chalky layer could not be observed in these early juvenile shells [51].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to most bivalves, C. gigas shell is made up of a shell-like foliae layer and lenses of chalk (Marie et al, 2011;Checa et al, 2018), a highly porous and poorly organized microstructure that is only found in Ostreidae (Mouchi et al, 2016;Checa et al, 2018). Recent structural and crystallographic observations have depicted that growth lines are continuous between the foliae and chalk, suggesting both layers are made simultaneously by different zones of the mantle tissue, where the foliated layer is made by the mantle edge and the chalky layer by the mantle pallial (Banker and Sumner, 2020). In oysters kept in low pH conditions, the outer epithelium of the mantle edge shows fewer AB-PAS positive cells compared with the mantle pallial zone, suggesting a decrease in the secretory activity in mantle cells underlying the foliated layer that possibly affects its formation.…”
Section: Ocean Acidification Provokes a Reduced Secretory Activity Of...mentioning
confidence: 99%
“…This suggests that the success of Sr labelling does not depend only on shell mineralogy, but that the mode of shell growth and the location of measurement plays an important role. In contrast to cockles and mussels, oysters show highly irregular growth patterns with frequent changes in growth rate and direction (Carriker et al, 1980;Banker and Sumner, 2020). Furthermore, oysters may resorb parts of their shell to maintain pH within the extrapallial fluid during anaerobic respiration, which may affect the timeline recorded in their outer shell layers (Kent, 1992).…”
Section: Variability Between Speciesmentioning
confidence: 99%